Stitz-Zeager_College_Algebra_e-book

Substituting x t and 2 2 3 1 y 1 t 2 into 2x 4y 6

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ion. Since we have a sum of squares and the squared terms have unequal coefficients, it’s a good bet we have an ellipse on our hands. (A parabola would have only one squared variable and a circle would have the same coefficient on the squared terms.) We need to complete both squares, and then divide, if necessary, to get the right-hand side equal to 1. x2 + 4y 2 − 2x + 24y + 33 x2 − 2x + 4y 2 + 24y x2 − 2x + 4 y 2 + 6 y 2 − 2x + 1 + 4 y 2 + 6y + 9 x (x − 1)2 + 4(y + 3)2 (x − 1)2 + 4(y + 3)2 4 (x − 1)2 + (y + 3)2 42 (x − 1) (y + 3)2 + 4 1 = = = = = 0 −33 −33 −33 + 1 + 4(9) 4 4 = 4 =1 =1 7.4 Ellipses 425 Now that this equation is in the standard form of Equation 7.4, we see that x − h is x − 1 so h = 1, and y − k is y + 3 so k = −3. Hence, our ellipse is centered at (1, −3). We see that a2 = 4 so a = 2, and b2 = 1 so b = 1. This means we move 2 units left and right from the center and 1 unit up and down from the center to arrive at points on the ellipse. Since we...
View Full Document

This note was uploaded on 05/03/2013 for the course MATH Algebra taught by Professor Wong during the Fall '13 term at Chicago Academy High School.

Ask a homework question - tutors are online